Factors Responsible for Delayed Enrollment for Anti-Retroviral Treatment - De R, Bhandari S, Roy S, Bhowmik A, Rewari BB, Guha SK (Journal of Nepal Health Research Council, 2013)
Background: Late presentation followed by delayed diagnosis and further delayed initiation of anti-retroviral therapy (ART) increases the risk of opportunistic infections and neoplasms among the HIV infected patients. Furthermore, this leads to not only poor response to therapy but also early death among them. Methods: An institution based cross-sectional study was undertaken to identify the factor(s) responsible for delayed registration for initiation of therapy among the HIV infected patients with absolute CD4 count <250 cells/μL based on self reports. ART naïve adult HIV patients (age ≥18 years) with baseline CD4 count of <250 cells/μL were included in this study. Results: Most patients 95 (95%) were unaware of the available ‘Integrated Counseling and Testing Centres’. Although 13 (13%) respondents had multiple reasons for delayed enrollment, majority 47 (47%) of the delays were due to the physician’s failure to suspect and refer them for HIV testing at the earliest opportunity. Other causes include health seeking behavior 13 (13%), fear of stigma 5 (5%), depression 3 (3%), and lack of family support 6 (6%). Conclusions: Even though delays in pre-ART enrollment have been realized since long, prevention efforts are poor, mostly due to the lack of understanding of the nature of the problem in its social context. Lack of clinical suspicion for HIV infection at the primary and secondary levels of health care still remains the most important reason for the delay. In order to prevent these delays in enrollments, intervention efforts need to be focused on not only the people infected with HIV but the primary health care providers as well, especially the practicing physicians.